Analgesic Effects of Thiamine in Male Long Evans Rats - Ainan, Sayema; Begum, Noorzahan; Ali, Taskina (Journal of Bangladesh Society of Physiologist, 2017)
Background: The concept of analgesic effects of thiamine along with other B vitamins has been supported since long by various clinical and experimental evidences, though effects of individual thiamine on pain are yet to be clearly demonstrated. Objective: To assess the effects of increasing doses of thiamine supplementation on pain. Methods: Forty-eight (48) male Long Evans rats (200±20 gm) were given thiamine (100, 200, 250, mg/kg/day; experimental) or normal saline (5 ml/kg/day; control) intraperitonealy (i.p) for 7 consecutive days. The analgesic activity was evaluated by three experimental pain models, hot (52±0.50C) water tail immersion test, the interphase (6th-15th minutes) of formalin (50?l, 2.5%, subcutaneous) test and acetic acid (2%, i.p) induced writhing test. Statistical analysis was done by ANOVA followed by Bonferroni post hoc test and p?0.05 was considered as significant. Results: In tail immersion test, %MPE significantly increased after 200 (p?0.05) and 250 (p?0.001) mg/kg of thiamine. In the formalin test, thiamine significantly lowered the jerking frequency (p?0.05, p?0.001, p?0.001, respectively) and duration of flexing and licking (p?0.001, in all doses), compared to control. In addition, in writhing test, significant increment in latency of appearance of 1st writhe (p?0.001, in higher 2 doses) and significant decrement in frequency of writhes (p?0.01, p?0.001, p?0.001, respectively, in all doses) were observed. Conclusion: The results of this study conclude that, repetitive administration of thiamine may cause alleviation of pain through central as well as peripheral inhibitory mechanisms, which is dose dependent as well. Bangladesh Soc Physiol. 2017, June; 12(1): 1-9